Augmented reality based mobile application for real-time Arabic language translation - Ouertani, Henda Chorfi; Tatwany, Lama (Communications in Science and Technology, 2019)
Augmented Reality (AR) technologies are nowadays widely and ubiquitously used to enhance our real world experience in novel and enriched ways. With the new generation of smart phones and AR technologies, we are embracing a stimulating way of Human-Computer Interaction. Many AR mobile applications were developed in many fields such as education, health, design and Translation... This paper deals with text translation. Many applications are proposed on the market but they are yet limited to a few number of languages. Arabic language is one of these unsupported ones. To overcome this shortage, an AR mobile application for real time Arabic text translation is developed. The user simply hover the device's camera on the desired text and it will be translated automatically and rapidly. This type of application consists of three main components which are: text detection, text extraction and text translation. To ensure the application is performing well, the application is tested on different datasets under different conditions. In addition, a user study test is conducted to test the usability and user satisfaction.